Diagnostic yield of hypertrophic cardiomyopathy in first-degree relatives of decedents with idiopathic left ventricular hypertrophy. Issue 4 (3rd February 2020) - Finocchiaro, Gherardo; Dhutia, Harshil; Gray, Belinda; Ensam, Bode; Papatheodorou, Stathis; Miles, Chris; Malhotra, Aneil; Fanton, Zeph; Bulleros, Paulo; Homfray, Tessa; Witney, Adam A; Bunce, Nicholas; et al.
Abstract: Aims: Idiopathic left ventricular hypertrophy (LVH) is defined as LVH in the absence of myocyte disarray or secondary causes. It is unclear whether idiopathic LVH represents the phenotypic spectrum of hypertrophic cardiomyopathy (HCM) or whether it is a unique disease entity. We aimed to ascertain the prevalence of HCM in first-degree relatives of decedents from sudden death with idiopathic LVH at autopsy. Decedents also underwent molecular autopsy to identify the presence of pathogenic variants in genes implicated in HCM. Methods and results : Families of 46 decedents with idiopathic LVH (125 first-degree relatives) were investigated with electrocardiogram, echocardiogram exercise tolerance test, cardiovascular magnetic resonance imaging, 24-h Holter, and ajmaline provocation test. Next-generation sequencing molecular autopsy was performed in 14 (30%) cases. Decedents with idiopathic LVH were aged 33 ± 14 years and 40 (87%) were male. Fourteen families (30%) comprising 16 individuals were diagnosed with cardiac disease, including Brugada syndrome ( n  = 8), long QT syndrome ( n  = 3), cardiomyopathy ( n  = 2), and Wolff–Parkinson–White syndrome ( n  = 1). None of the family members were diagnosed with HCM. Molecular autopsy did not identify any pathogenic or likely pathogenic variants in genes encoding sarcomeric proteins. Two decedents had pathogenic variants associated with long QT syndrome, which were confirmed in relatives with the clinical phenotype. One decedent had a pathogenic variant associated with Danon disease in the absence of any histopathological findings of the condition or clinical phenotype in the family. Conclusion : Idiopathic LVH appears to be a distinct disease entity from HCM and is associated with fatal arrhythmias in individuals with primary arrhythmia syndromes. Family screening in relatives of decedents with idiopathic LVH should be comprehensive and encompass the broader spectrum of inherited cardiac conditions, including channelopathies.